Detection of chemical drug adulterants in herbal supplements: A GC-MS identification of paracetamol, prednisone, and prednisolone - Pratama, Mohammad Anrico Putra (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Traditional Medicine and Health Supplements are products intended to provide health benefits because they are made based on herbal ingredients that do not contain Chemical Drugs/Bahan Kimia Obat (BKO), but sometimes there are some Chemical Drugs/Bahan Kimia Obat (BKO) detected in Traditional Medicine and Health Supplements such as Paracetamol, Prednisone, and Prednisolone. Methods: Identification of the three compounds was carried out using the Gas Chromatography Mass Spectrometry method. Sample codes 0014A and 0014B have retention times and areas that are not the same as the standard solutions of the three compounds. Findings: The presence of these three compounds makes Traditional Medicine and Health Supplements dangerous if they exceed the specified requirements. Conclusion: The identification results of Paracetamol show a retention time value of 9,559 and an area of ​​169 for sample code 0014A, in sample 0014B no retention time and area were detected. In the identification of Prednisone and Prednisolone, both samples 0014A and 0014B no retention time and area were detected, so it can be said that the samples meet the requirements and are suitable for consumption by the public. Novelty/Originality of this article: Based on the analysis method (103/OTSK/MA-PPPOMN/20) states that the determination of the detection limit (LOD) for Paracetamol is 4.32 µg/g (solid preparation) and 2.02 µg/mL (liquid preparation), for Prednisone is 25.18 µg/g (solid preparation) and 11.78 µg/mL (liquid preparation), and Prednisolone is 86.86 µg/g (solid preparation) and 40.63 µg/mL (liquid preparation).